Updates in the management of connective tissue disease-associated interstitial lung disease - Chengappa Kavadichanda; G S R S N K Naidu (Indian Journal of Rheumatology)
The occurrence of interstitial lung disease (ILD) in a setting of a well-defined autoimmune disease or in the presence of autoantibodies is being increasingly recognized. The traditional approach to the treatment of connective tissue disease-associated ILD (CTD-ILD) was a combination of glucocorticoids and cyclophosphamide or mycophenolate mofetil. Most of the evidence in treating these cases is limited to a few trials in scleroderma and idiopathic pulmonary fibrosis along with several observational studies in other CTDs. Insights into the pathology of these diseases and the associated lung involvement have resulted in the emergence of several immunosuppressive, antifibrotic, and small molecules as alternatives in CTD-ILD. In this review, we have attempted to summarize several emerging therapeutic options for CTD-ILD.